Efektivitas Plant Growth Promoting Rhizobacteria (PGPR) Akar Bambu Tallang Terhadap Produksi Tanaman Kacang Tanah (Arachis Hypogaea L.) - Pemyatri Sesilia; Kornelius Ture; Yusuf La’langan Limbongan; Adewidar Marano Pata’dungan; Sepsriyanti Kannapadang; Willy Yavet Tandirerung (Jurnal Riset Rumpun Ilmu Tanaman, 2025)
Plant Growth Promoting Rhizobacteria (PGPR) is a group of microorganisms that colonize plant roots and play an important role as a biostimulant, biofertilizer, and bioprotectant that can increase plant growth and productivity. This study aims to determine the effectiveness of Tallang bamboo root PGPR on the growth and production of peanut plants (Arachis hypogaea L.) elephant variety. The study was conducted from March 2025 to July 2025 in Lion Tondok Iring Village, North Makale District, Tana Toraja Regency, at an altitude of 828 meters above sea level. The research method used a Randomized Block Design (RBD) with one treatment factor, namely the concentration of Tallang bamboo root PGPR, which consisted of four treatment levels: P0 = without Tallang bamboo root PGPR (control), P1 = 15 ml/L water, P2 = 30 ml/L water, and P3 = 45 ml/L water. The variables observed included the number of pods per plant, fresh weight of pods per plant, dry weight of pods per plant, seed weight per plant, seed weight per plot, seed yield per hectare, and harvest index. The results showed that the application of Tallang bamboo root PGPR at a concentration of 30 ml/L water (P2) had the best effect on all growth and yield parameters, namely the number of pods per plant, fresh weight of pods per plant, dry weight of pods per plant, seed weight per plant, seed weight per plot, seed yield per hectare, and harvest index, compared to the control or other concentration treatments. Thus, it can be concluded that the application of Tallang bamboo root PGPR at a concentration of 30 ml/L water is the most effective dose to increase the growth and production of Gajah variety peanut plants.